Chapter Una dottrina rivoluzionaria della sistemazione dello spazio. Massimo Quaini geografo-pianificatore - Dematteis, Giuseppe (Territori, 2021)
The idea of a planning-oriented geography was part of the 'revolutionary' renewal program of the discipline proposed by Massimo Quaini since the 70's. First through an analysis of how human geography was built in the seventeenth and nineteenth centuries, then in the theoretical and methodological writings in which he critically examines his experiences as a geographer engaged in urban, regional, environmental and landscape planning works. In such writings, he highlights the latent and unsolved contrast between the aim of meeting the needs of the inhabitants and the tendency to organize the local space according to economic competition.